An approach for distributed discussion and collaborative knowledge sharing: Theoretical and empirical analysis. (February 2019) - Agis, Ramiro A.; Gottifredi, Sebastian; García, Alejandro J.
Highlights: Collaborative discussion and knowledge acquisition strategy for distributed agents. Agents end the discussion with the same assessment about the shared information. Agents can freely and dynamically join or leave the discussion. Structured argumentation is used for knowledge representation and reasoning. The strategy is formally characterized and empirically analysed. Abstract: We present a strategy for collaborative reasoning and automatic knowledge sharing in which multiple agents discuss about some piece of information until they reach an agreement. A structured argumentation system (DeLP) is used as the underlying knowledge representation and reasoning formalism, allowing agents to contribute to the discussion by posing or rejecting arguments, or objecting to atomic information. In this proposal, in order to be able to represent more general scenarios than other approaches in the literature, agents are allowed to believe in strict information and are allowed to freely join and leave the discussion at any moment. The proposed strategy automatically deals with the conflicts that may arise when agents pose contradictory strict information, which have to be solved to maintain the soundness of the discussion. The operational semantics of the strategy is defined using a transition system to formally characterise the agents' behaviour and to prove its properties. An empirical comparison between the performance of different criteria that the agents can follow during the discussion is presented.